A Cell Wall Hydrolase MepH Is Negatively Regulated by Proteolysis Involving Prc and NlpI in Escherichia coli - Jeon, Wook-Jong; Cho, Hongbaek (Frontiers in Microbiology, 2022)
Cell wall assembly of Gram-negative bacteria requires DD-endopeptidase activity that cleaves peptidoglycan (PG) crosslinks in addition to PG synthetic activity, and the activity of DD-endopeptidases needs to be tightly regulated to maintain cell wall integrity during PG expansion. Among the major DD-endopeptidases functioning for PG assembly in Escherichia coli, MepS and MepM have been shown to be negatively controlled by the periplasmic protease Prc. In this study, we performed a genetic selection using the synthetic lethality between the mepS and mepM mutations in rich medium to uncover regulatory mechanisms controlling the activity of DD-endopeptidases other than MepS and MepM. This selection revealed mutations in prc and nlpI as suppressors. Gene deletion analyses revealed that MepH is required for suppression of the MepS¬— MepM— growth defect by the prc or nlpI mutation. We also discovered that MepH is directly degraded by Prc and that this degradation is further promoted by NlpI. Thus, our study showed that all three DD-endopeptidases which play major roles in PG assembly of E. coli under normal physiological conditions are controlled by a common periplasmic protease.